PENERAPAN MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN GAME BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK - Rilla Juni Isra; Radhya Yusri; Anna Cesaria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low mathematics learning outcomes of students in Vocational High Schools (SMKs) remain a significant issue that requires serious attention. This problem is primarily caused by learning processes that do not fully engage students actively and by the limited use of varied and innovative learning models. This study aimed to determine the effect of implementing the Problem-Based Learning (PBL) model combined with a Game-Based Learning (GBL) approach on the mathematics learning outcomes of Year 11 students at SMKN 1 Simpang Alahan Mati, Pasaman Regency. This research employed a quantitative approach using a true experimental method with a post-test-only control group design. The sample consisted of two classes: Year 11 Computer and Network Engineering (TKJ) as the experimental group, which received instruction through the PBL model with a GBL approach, and Year 11 Motorcycle Engineering (TSM) as the control group, which received conventional instruction. The research instrument was a mathematics achievement test that had been tested for validity and reliability. Data were collected through the administration of a post-test after the learning treatments had been implemented. Data analysis was conducted using the non-parametric Mann–Whitney test because the data were not normally distributed. The findings revealed a significant difference in mathematics learning outcomes between the experimental and control groups. The mean score of the experimental group was 87.67, which was higher than that of the control group, 70.45. Therefore, it can be concluded that the implementation of the PBL model with a GBL approach is effective in improving students’ mathematics learning outcomes and in creating a more active, engaging, and meaningful learning environment.